Analisis Pengaruh Karakteristik Komite Audit Dan Whistleblowing System Terhadap Potensi Terjadinya Fraud Pada Bumn Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Sakinah, Dwi Aprilia; Meuthia, Reno Fithri; Dwiharyadi, Anda (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2023)
This study aims to examine the effect of audit committee independence, number of audit committee meetings, audit committee financial expertise and whistleblowing system on the potential for fraud. The study population is State-Owned Enterprises (SOEs) listed on the IDX in 2020-2022. Samples were determined by purposive sampling and 20 samples were obtained. The hypothesis in this study was tested using multiple linear regression. The results showed that the independence of the audit committee did not affect the potential for fraud. The number of audit committee meetings, audit committee financial expertise, and whistleblowing system affect the potential for fraud. The implications of this research can be useful as a consideration for companies in making policies related to the potential for fraud.